Ekonomi Kreatif Berbasis Digital Dan Dampak Terhadap Kesejahteraan Sosial Ekonomi Masyarakat Di Sekitaran Danau Perintis - Ahmad, Hawai; Eraku, Sunarty Suli; Kobi, Wiwin (Universitas Negeri Gorontalo, 2026)
The area holding significant potential for digital-based creative economy development is the Perintis Lake tourist destination in Bone Bolango Regency, Gorontalo Province. This area represents one of the region's premier tourism destinations and provides livelihoods for surrounding communities through culinary trade, tourism services, photography, and souvenir sales. This research aims to analyze the role of digitally-based creative economies on the socioeconomic well-being of communities around the Perintis Lake tourist area in Bone Bolango Regency. Research on digitally based creative economies has a significant and positive impact on improving the socio-economic welfare of communities. The utilization of digital technology, particularly through social media, e-commerce platforms, and digital payment systems like QRIS and e-wallets, has proven capable of expanding market reach and increasing income for local businesses. Digital media serves as a means of promotion and business transactions, resulting in increased household income, new job opportunities, and greater economic stability for families within the digitally based creative economy.